Assessing the influence of astronomical phenomena on the Earth. Issue 67 (17th July 2015) - Feng, F.; Bailer-Jones, C.A.L.
Abstract : The temporal evolution of the terrestrial impact cratering rate over the past 250 Myr is dominated by a trend increasing towards the present. We find that the Sun's motion through the Galaxy plays at best a minor role in modulating this cratering rate. Moreover, the solar apex motion can explain the non-uniform longitude distribution of the perihelia of long period comets without invoking a solar companion in the outer Oort cloud.